PERANCANGAN SISTEM INFORMASI PENJUALAN PADA TOKO ONLINE SOUTHEAST TIGER - Shintya Ayu Malinda, - (2020)
Sales information system is one way to improve the quality of service in buying and selling activities through the internet especially the quality more detailed information about the product, many sales businesses, especially clothing product, use sales information system, to facilitate the sales process. Southeast Tiger still applies the sales system manually so there is still a lack of quality service provided to customer. This designation aims to facilitate Southeast Tiger in managing transaction processes, conducting data collection and increasing sales revenue. This design and research uses prototyping method and uses HTML and PHP programming language and uses MySql as a database. With the design of the sales information system, it will facilitate Southeast Tiger in the sales process.